Psychiatric disorders and suicidal behaviour in patients seen at a transgender clinic in Cape Town, South Africa - Dangor, Fatima (Department of Psychiatry and Mental Health, 2023)
Background: International research indicates that due to the impact of stigma, marginalisation and discrimination, transgender individuals are a vulnerable population at risk of psychiatric disorders and suicidal behaviour. Despite this, there is a lack of research on the prevalence of mental health conditions and suicidal behaviour amongst transgender individuals in South Africa. Aim: To assess the prevalence of psychiatric disorders and suicidal behaviour in transgender individuals seen at the Transgender Clinic at Groote Schuur Hospital. To provide an improved understanding of the mental health needs of individuals attending the TGC. Setting: This study was conducted at the multidisciplinary Transgender Clinic at Groote Schuur Hospital, South Africa. Methods: The study was a retrospective folder review of individuals attending the clinic from November 2018 until December 2019. Results: 44 individuals attended the clinic during the study, all of which were included in the analysis. Depression was the most commonly self-reported symptom (n=13, 29.5%). Other common symptoms included those of panic and generalised anxiety (n=10, 22.7%). After assessment at the TGC, thirty-one (70.5%) individuals met the criteria for a psychiatric disorder. Mood disorders were the most common DSM–5 diagnoses (n=28, 63.6%). Thirteen (41.9%) individuals with a current psychiatric disorder were on treatment. Almost three-quarters of the individuals (n=32, 72.7%) reported alcohol consumption, of which only 2 individuals (4.5%) reported regular daily consumption. Twenty-one individuals were tobacco smokers (47.7%), and approximately one-third used cannabis (n=16, 36.4%). Eighteen (40.9%) individuals reported suicidal behaviour, and fourteen (31.8%) non-suicidal self-injury. ix Conclusion: Transgender individuals attending the GSH Transgender Clinic had a high prevalence of psychiatric disorders and suicidal behaviour. Our improved understanding of the mental health needs of individuals attending the Transgender Clinic will better inform future gender affirming care. Keywords: gender non-conforming; mental health; non-suicidal self-injury; psychiatric disorders; South Africa; suicidal behaviour; transgender